THE IMPACT OF CREDIT RISKS ON RAISING THE ANNUAL INTEREST RATE ON INVESTMENT LOANS-A CASE STUDY OF THE INTERNATIONAL DEVELOPMENT BANK (IDB) - Dr. Dukhkhan Adil Bashir Dhahir I; Dr. Omer Adeeb Qassim; Dr. Siraj Razooqi Abbas (Scholars Digest Publishing, 2024)
Banks seek international development IDB to achieve its strategic goals in light of an investment climate that secures it to achieve those goals and the least risks and one of the most important areas of the annual interest rate on investment loans attractive to banks is the process of granting credit risks, which is considered the most profitable banking operations and at the same time banks must maintain a sufficient liquidity ratio to manage other banking activities and operations and overcome liquidity risks while achieving appropriate profits,  The research acquires its importance from the importance of banking credit risks for financial and banking institutions, which is reflected in the economic performance as a whole, as well as the importance of the annual interest rate on banking investment loans, which moves the wheel of the economy and exploits the available resources, from here emerged the problem of the study, which is that the international development banks. IDB suffers in its operations credit risks from its inability to grant credit risk or that the credit risk granted does not rise to achieve profits in raising the level of the annual interest rate on bank investment loans, and the study started from the premise that bank credit has positive repercussions in raising the annual interest rate on bank investment loans and achieving profits The study aims to show the role played by credit risk for banks Research sample and its impact on performance rate The annual interest rate on investment loans for these banks, and the research relied on the method of descriptive inductive approach in addition to the statistical standard approach, and the study reached some conclusions and provide some recommendations to the banks of the study sample and others.
Keywords: Credit Risk, Interest Rate, Investment Loans, International Development Bank (IDB)